Pregnancy outcome of anti‐HCV direct‐acting antivirals: Real‐life data from an Egyptian cohort. (11th May 2021) - AbdAllah, Mohamed; Alboraie, Mohamed; Abdel‐Razek, Wael; Hassany, Mohamed; Ammar, Islam; Kamal, Ehab; Alalfy, Mahmoud; Okasha, Ahmed; El Akel, Wafaa; Shaaban, Elsaied; Elbaz, Tamer; Hefny, Zeinab; et al.
Abstract: We aimed to assess the pregnancy outcome in women with chronic HCV who had negative pregnancy test prior to the anti‐HCV course and had unintended pregnancy while on HCV treatment. Hundred patients with a mean age of 30 ± 6.7 y were included and advised to withhold antivirals and continue follow‐up in viral hepatitis and obstetrics centres till delivery. All patients received a 12‐weeks regimen of anti‐HCV [sofosbuvir plus daclatasvir (SOF/DCV): n = 95, SOF/DCV plus ribavirin: n = 3, and paritaprevir/ritonavir/ombitasvir plus ribavirin: n = 2]. Only nine patients completed the full antiviral course against medical advice, and 91 stopped between on‐treatment weeks 4 and 8. Eighty‐eight patients delivered full‐term babies, eight had preterm babies and two had abortions. Of the nine patients who completed the full course of DAAs, seven (77.8%) delivered normal babies, attended their post‐treatment week 12 visit, and all (100%) achieved sustained virological response. No major antiviral‐related adverse events were reported.